Comparative Historical Perspectives of the Status of Women - Badli Shah, Nik Noriani Nik (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Comparative Historical Perspectives of the Status of Women